Effect of brown and green seaweeds on diet digestibility, ruminal fermentation patterns and enteric methane emissions using the rumen simulation technique - Roskam, Emily; Kirwan, Stuart F.; Kenny, David A.; O’Donnell, Caroline; O’Flaherty, Vincent; Hayes, Maria; Waters, Sinéad M. (Frontiers in Animal Science, 2022)
Inclusion of the red seaweed Asparagopsis taxiformis as a feed additive, has led to significant reductions in methane (CH4) production from ruminants. However, dietary supplementation with this seaweed is negatively associated with health and environmental concerns mainly due to its bromoform content, a potential carcinogen. The objective of this study was to investigate the effects of brown and green seaweeds on diet digestibility, ruminal fermentation patterns, total gas (TGP) and CH4 production in vitro, using the RUSITEC. In experiment 1, Pelvetia canaliculata (PEC) was examined. In experiment 2, Cystoseira tamariscifolia (CYT), Bifurcaria bifurcata (BIB), Fucus vesiculosus (FUV), Himanthalia elongata (HIM) and Ulva intestinalis (ULI) were analysed. Ascophyllum nodosum (ASC) was included in both experiments. A diet containing A. taxiformis (ASP1; ASP2) and an unsupplemented diet (CON) were included as positive and negative controls, respectively in both experiments. Seaweeds were included at a rate of 10g/kg dry matter (DM) into a control diet of 50:50 (w:w) forage:concentrate. The seven brown and green seaweeds assessed failed to affect absolute CH4 emissions or alter fermentation patterns. In experiment 1, seaweed treatment had no effect on diet digestibility, CH4 %, CH4 mmol/d or CH4 L/d (P>0.1), however ASP1 reduced CH4 mmol/g DOM by 49% (P<0.01) relative to the control. Both ASC and ASP1 tended to increase TGP (P<0.1) relative to the control. In addition to this, the inclusion of seaweed in experiment 1 reduced the production of NH3-N (P<.0001) compared to the control. (In experiment 2, seaweed treatment had no effect on diet digestibility or TGP. Both ASP2 and FUV reduced CH4% (P<0.01) but only ASP2 significantly reduced CH4 mmol/d, CH4 L/d and CH4 mmol/g DOM (P<0.05). Daily mMol butyrate was reduced by ASP2 relative to the control and most other seaweeds (P<.0001). In both experiment 1 and 2, seaweed inclusion had no effect on daily total VFA, acetate or propionate production or the acetate:propionate ratio relative to the control. To conclude, including the bromoform-free brown and green seaweeds at 10g/kg DM has no negative effects on diet digestibility or fermentation patterns but also failed to reduce the production of enteric CH4 in vitro.